Blocking Intermediate-Conductance Calcium-Activated Potassium Channels in the Macrophages Around Ganglionated Plexi Suppresses Atrial Fibrillation Vulnerability in Canines With Rapid Atrial Pacing - Ma, Yazhe; Fu, Yuntao; Wang, Youcheng; Yang, Mei; Yao, Yajun; He, Shanqing; Liu, Dishiwen; Cao, Zhen; Wang, Xi; Tang, Yanhong; Zhao, Qingyan; Huang, Congxin (Frontiers in Physiology, 2022)
Previous studies have indicated that ganglionated plexi (GP) function influences atrial fibrillation (AF) vulnerability, and intermediate-conductance calcium-activated potassium channels (SK4) have a close relationship with cardiomyocyte automaticity and the induction of AF. However, the effects of the SK4 inhibitor on GP function and AF vulnerability are unknown. Eighteen beagles were randomly divided into a control group (n = 6), rapid atrial pacing (RAP) group (n = 6), and triarylmethane-34(TRAM-34, an SK4 inhibitor) group (n = 6). TRAM-34 (0.3 mL,15 mmol/L) and saline were locally injected into GPs in the TRAM-34 group dogs and dogs from the other groups, respectively. After that, dogs in the RAP and TRAM-34 groups were subjected to RAP, and the neural activity of anterior right GP (ARGP) and atrial electrophysiology were measured. The levels of inflammatory cytokines and function of macrophages in the ARGP were measured in the three groups. At 10 min after TRAM-34 injection, ARGP activity and atrial electrophysiology did not significantly change. The atrial pacing shortened effective refractory period (ERP) values at all sites and increased the AF vulnerability and ARGP neural activity, while TRAM-34 reversed these changes. The levels of CD68+ cells, induced nitric oxide synthase (iNOS), interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α in the ARGP tissues were higher in the RAP group and TRAM-34 group than they were in the control group. Furthermore, the levels of the CD68+ cells, iNOS, and inflammatory cytokines in the ARGP tissues were higher in the pacing group than those in the TRAM-34 group. Based on these results, administration of TRAM-34 into the atrial GP can suppress GP activity and AF vulnerability during atrial pacing. The effects of TRAM-34 might be related to macrophage polarization and the inflammatory response of GP.